2015
DOI: 10.1002/hed.24097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for flap loss and salvage in free flap head and neck reconstruction

Abstract: Although flap salvage should be attempted, multiple attempts are not recommended, especially for muscle-only flaps. Combined arteriovenous and late thrombosis has a dismal prognosis regardless of different salvage techniques. © 2015 Wiley Periodicals, Inc. Head Neck 38: E771-E775, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 21 publications
8
90
4
Order By: Relevance
“…Similarly, we also found that venous occlusion was significantly more common than arterial thrombosis (100% vs 0%; P < .01). In this series, the overall free fibula flap success rate of 96.9% and salvage rate of 62.5% is comparable with other larger studies regarding free tissue transfer for head and neck reconstruction …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly, we also found that venous occlusion was significantly more common than arterial thrombosis (100% vs 0%; P < .01). In this series, the overall free fibula flap success rate of 96.9% and salvage rate of 62.5% is comparable with other larger studies regarding free tissue transfer for head and neck reconstruction …”
Section: Discussionsupporting
confidence: 84%
“…The osteocutaneous free fibula flap is the primary option for reconstruction after a segmental mandibulectomy because of the large amount of bone stock and reliable skin paddle. With the recent advent of new technologies, mandibular reconstruction with free fibula flaps can be performed reliably with excellent rates of success and low risk of complications . Yet, loss of a free fibula flap can still occur as a result of factors not detected during the preoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakatsuka et al performed 2,372 free tissue transfer cases and described a low cumulative incidence of total complications (17.0%), partial flap necrosis (2.5%), and total flap necrosis (4.2%) . Chang et al describe a similar experience at their high‐volume institution, respectively (n = 2296: not recorded, 0.6%, 2.6%) . Therefore, AHNS SCF surgeon responses do not appear to align with the overwhelmingly positive description of published SCF outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these advancements, overall flap success rates exceed 95% at multiple institutions . However, free flap complications, most commonly by vascular thrombosis, can have devastating effects on morbidity and functional prognosis . For vascular thrombosis, early recognition of vascular compromise is associated with improved salvage rates .…”
Section: Introductionmentioning
confidence: 99%